Frontispiece: Photon Energy Becomes the Third Dimension in Crystallographic Texture Analysis. Issue 40 (19th September 2016) - Grünewald, Tilman A.; Rennhofer, Harald; Tack, Pieter; Garrevoet, Jan; Wermeille, Didier; Thompson, Paul; Bras, Wim; Vincze, Laszlo; Lichtenegger, Helga C.
Abstract : Crystallographic Texture . H. C. Lichtenegger et al. describe in their Communication onpage 12190 ff. a method to determine crystallographic texture. The method is based on energy‐dispersive Laue diffraction and enables 3D information to be obtained without sample rotation.